Evaluation Of Physical Education Independent Curriculum Through CIPP: Managerial Implementation In Learning Activities - Wahidah, Ida; Listyasari, Endah; Rahmat, Agus Arief; Rohyana, Aang (Indonesian Journal of Sport Management, 2023)
The government has created an independent curriculum as a learning recovery, but not all schools implement it well. Therefore, an evaluation is needed, especially regarding the management of learning activities. The purpose of this study is to evaluate the implementation of the independent curriculum model in physical education subjects at State Vocational Schools in Tasikmalaya City. This research used a qualitative descriptive approach. In this study, data were collected through triangulation techniques consisting of observation, semi-structured interviews, and documentation. This study involved the vice principal for curriculum, four physical education teachers, and four students. They were selected through a purposive sampling technique. Data analysis involved preparation, inference, and verification. The results showed that the context evaluation of goals and objectives indicators and strength indicators had been fulfilled. However, weakness indicators related to teacher consistency in implementing learning still exist. Input evaluation on indicators of curriculum structure, PE teacher competence, teaching materials, and students have been fulfilled and run well. However, input evaluation on indicators of infrastructure availability still needs to support the continuity of PE learning. Process evaluation on indicators of implementation and implementation of assessments has gone well, but product evaluation on indicators of program achievement still needs to be improved. Implementing CIPP managerial evaluation is carried out by ensuring that the evaluation is carried out systematically, periodically, and comprehensively. Evaluation results are used as the basis for decision-making related to the improvement and development of the Physical Education curriculum. Teachers and school management play an active role in ensuring the sustainability and effectiveness of the evaluation.